Exploring MAS: A Reliable Molecular tool for Development of Multiple Disease Resistance in Tomato (Solanum lycopersicum L.) through Gene Pyramiding - Oladokun, John Oladeji; Mugisa, Immaculate (International Journal of Environment, Agriculture and Biotechnology, 2019)
Tomato is principally subjected to severe yield losses due to adverse effects of a number of factors particularly biotic factors (pathogens). The lacks of tomato genotypes resistance to diseases have increased both the financial cost and environmental impact of tomato production while reducing the yield and quality. Therefore developing tomato genotypes with multiple resistances to diseases is a desirable goal. However, the most effective strategy of controlling reduction in yield and quality of tomato caused by various biotic factors during crop productivity encountered by poor resource farmers is by utilization of host resistance. Recently, technological advancement has led to the development of DNA based molecular markers closely linked to genes in tomato chromosomes that bestowed resistance to various kinds of biotic factors. Gene transfer of preferred traits into a single tomato genotype is now possible through the deployment of marker assisted selection (MAS) process, which now hastens the advancement of resistance tomato cultivars in its lowest population with gene pyramiding or stacking. In this review, we present the eco-friendly molecular tools with emphases on MAS for the improvement of biotic resistance in tomatoes which can be more explore in identifying land races that have the potentials of subduing the attack of pathogens if improved genetically.